Porphyrinoid dyes for photodynamic anticancer and antimicrobial therapy treatments - Soy, Rodah Cheruto (Rhodes University, Faculty of Science, Department of Chemistry)
The search for alternative therapies and non-toxic photosensitizer drugs that can efficiently generate cytotoxic reactive oxygen species for biomedical applications, such as in alternative photodynamic therapy (PDT) for cancer treatment and photodynamic antimicrobial chemotherapy (PACT) for drug-resistant bacteria treatment is on the rise. Nevertheless, the lack of photosensitizer dyes that absorb light strongly within the therapeutic window (620âˆ’850 nm) that can locally target the tumor and bacterial cells and generate singlet oxygen efficiently are some of the main challenges in PDT and PACT treatment. This study sought to address the challenges that impede PDT and PACT from realizing their full potential by synthesizing a series of meso-aryltetrapyrrolic photosensitizer dyes that absorb light within the therapeutic window. These include meso-tetraarylporphyrin (Por), A3-type meso-triarylcorrole (Cor), meso-tetraarylchlorin (Chl), and N-confused meso-tetraarylporphyrin (NCP) dyes with 4-thiomethylphenyl (1), thien-3-yl (2), thien-2-yl (3), 5-bromo-thien-2-yl (4), 4-methoxyphenyl (5), 3-methoxyphenyl (6), 4-hydroxyphenyl (7) and 4-hydroxy-3-methoxyphenyl (8) meso-aryl rings. Por, Cor, Chl and NCP dyes and and their Ga(III), P(V), In(III) and/or Sn(IV) complexes with 1-8, 1-4, 5-8 and 5 meso-aryl rings were studied, along with two A2B-type Ga(III) meso-triarylcorroles with pentafluorophenyl rings at the A2 positions and 3,6-di-t-butyl-9H-carbazole (9) or N-butyl-4-carbazole (10) rings at the B position that were prepared in the laboratory of Prof. Xu Liang of Jiangsu University in the People's Republic of China. The carbazole nitrogen of 10-GaCor was quaternized at Rhodes University with ethyl iodide to form a cationic species (10-GaCor-Q) for PDT and PACT activity studies. The structures of the synthesized dyes were confirmed using UV-visible absorption and 1H NMR spectroscopy, and MALDI-TOF-mass spectrometry. 1-4-InPor In(III) porphyrins, 1-4-PVCor, 1-4-GaCor A3 PV and GaIII corrole dyes were also conjugated to gold nanoparticles (AuNPs) and silver nanoparticles (AgNPs) via sulfur-gold and sulfur-silver affinities. The successful conjugation of the dyes onto the nanoparticles to form dye-AuNP or dye-AgNP nanoassemblies was confirmed using transmission electron microscopy (TEM), energy dispersive X-ray (EDX) spectroscopy, X-ray powered diffraction (XRD), and (X-ray photon spectroscopy) XPS. The photophysicochemical, photostability, and lipophilicity properties of the dyes and their PDT and PACT activities were investigated, and the structure-property relationships were analyzed. This was accomplished by analyzing the changes in the properties of the dyes due to the meso-aryl substituents, central ions, molecular symmetry, and heavy atom effects. Time-dependent-density functional theory (TD-DFT) calculations were also used to further probe the electronic and optical spectroscopic properties of the dyes. The analysis of the photophysicochemical, photostability, and lipophilicity data for the synthesized dyes demonstrated that there are inherent structure-property relationships for the dyes studied. The TD-DFT calculations also assisted in rationalizing the observed optical spectroscopic data for the dyes. The introduction of different meso-aryl substituents resulted in minor absorption spectral changes on the parent structures of the dyes due to their inductive and mesomeric effects, while the insertion of Ga(III), In(III), and Sn(IV) electropositive metal centers resulted in marked red shifts of the B bands due to favorable interactions with the porphyrin or porphyrinoid ligand core. The lower symmetries of the corrole, chlorin, and N-confused porphyrin dyes resulted in enhanced absorption properties within the therapeutic window relative to porphyrins. The heavy atom effect from the Ga(III), In(III), and Sn(IV) central ions, the meso-aryl groups, and the external heavy atom effect from the AuNPs and AgNPs significantly reduced the fluorescence quantum yield values of the dyes resulting in high singlet oxygen quantum yields. The dye complexes also exhibited properly balanced lipophilic properties and high photostabilities. The P(V) ion of the A3 PV corrole dyes reduced the aggregation effects, enhanced cellular uptake, and lowered the lipophilicity values relative to the A3 GaIII corrole dyes. The porphyrin and porphyrinoid complexes studied exhibited relatively low in vitro dark cytotoxicity toward MCF-7 cancer cells, which is enhanced for AuNP nanoconjugates of 1-InPor, 1-3-PVCor, and 1-3-GaCor. The dyes also have low in vitro dark cytotoxicity toward planktonic and biofilm cells of S. aureus and E. coli. The complexes also exhibited favorable PDT and PACT activities toward MCF-7 cancer cells, and planktonic and biofilm S. aureus and E. coli bacteria due to their high singlet oxygen quantum yields. AuNP and AgNP nanoconjugates of 1-4-InPor, 1-4-PVCor, and 1-4-GaCor exhibited enhanced PDT and PACT activities due to the favorable synergistic effects of nanoparticles. The PDT and PACT activities of A3 PV corrole dyes and the nanoconjugates of 1-4-PVCor are slightly higher than those of A3-type GaIII corroles and their nanoconjugates due to decreased aggregation effects and enhanced PS drug uptake. The cationic 10-GaCor-Q species also exhibit favorable PDT and PACT activities in contrast to the neutral 9-10-GaCor dyes due to enhanced PS drug penetration into the tumor or bacteria cells. The complexes also exhibited high Log10 reduction values for planktonic S. aureus suggesting that the dyes are highly efficient PS dyes. The activities of the complexes toward planktonic E. coli bacteria are moderate except for 10-GaCor-Q, 2-4-PVCor-AgNPs, and 5-8-SnChl chlorins exhibiting relatively favorable activity with > 3 Log10 CFU.mLâˆ’1 values. The dyes also exhibit moderate activities toward the S. aureus and E. coli biofilm cells, which are lower than for the planktonic cells, as shown by their lower Log10 reduction values. The data demonstrate that the low symmetry corrole, chlorin, and N-confused porphyrin complexes that absorb light strongly within the therapeutic window have significantly enhanced PDT and PACT activities relative to their porphyrin analogs.
Keywords: Porphyrins; Corrole; Chlorin; Photochemotherapy; Active oxygen; Photophysics; Photosensitizing compounds